Water governance, policy and knowledge transfer : international studies in contextual water management - Boer, Cheryl de, editor; Kruijf, Joanne Vinke-de, editor; editor; Bressers, Hans. (Abingdon, Oxon : Routledge, 2013)
Includes bibliographical references and index